2004
DOI: 10.1007/s00425-004-1204-y
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of a ubiquitously expressed pectin methyl esterase in Solanum tuberosum L. affects plant growth, leaf growth polarity, and ion partitioning

Abstract: Two pectin methyl esterases (PMEs; EC 3.1.1.11) from Solanum tuberosum were isolated and their expression characterised. One partial clone ( pest1) was expressed in leaves and fruit tissue, while pest2 was a functional full-length clone and was expressed ubiquitously, with a preference for aerial organs. Potato plants were transformed with a chimeric antisense construct that was designed to simultaneously inhibit pest1 and pest2 transcript accumulation; however, reduction of mRNA levels was confined to pest2. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
37
0

Year Published

2005
2005
2018
2018

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 55 publications
(38 citation statements)
references
References 39 publications
(48 reference statements)
1
37
0
Order By: Relevance
“…Indeed, over-expression of pectin methylesterase inhibitors results in longer root cells (Lionetti et al, 2007). Therefore, the degree of methylation and demethylation of pectin determines the delicate balance between cell wall extensibility and rigidity with consequent effects on growth and shape of cells (Burton et al, 2000;Pilling et al, 2004;Lionetti et al, 2007;Wolf et al, 2009;Xiao and Anderson, 2013;Kim et al, 2015). Consistent with this notion, overexpression of pectin methyltransferases, CGR2 or CGR3, led to enhanced rosette size and fresh weight in Arabidopsis (Kim et al, 2015).…”
mentioning
confidence: 95%
See 1 more Smart Citation
“…Indeed, over-expression of pectin methylesterase inhibitors results in longer root cells (Lionetti et al, 2007). Therefore, the degree of methylation and demethylation of pectin determines the delicate balance between cell wall extensibility and rigidity with consequent effects on growth and shape of cells (Burton et al, 2000;Pilling et al, 2004;Lionetti et al, 2007;Wolf et al, 2009;Xiao and Anderson, 2013;Kim et al, 2015). Consistent with this notion, overexpression of pectin methyltransferases, CGR2 or CGR3, led to enhanced rosette size and fresh weight in Arabidopsis (Kim et al, 2015).…”
mentioning
confidence: 95%
“…The plant cell wall controls expansion and positioning of cells of photosynthetic tissues and therefore, changes in cell wall properties will have a direct impact on the above properties. Although there is evidence for changes in leaf architecture as a result of alterations in genes that affect the synthesis and properties of the cell wall (Burton et al, 2000;Kim and Delaney, 2002;Pilling et al, 2004;Wolf et al, 2009;Kim et al, 2015), an in-depth analysis of effects on leaf gas exchange and overall plant growth under such circumstances has not yet been conducted.…”
mentioning
confidence: 99%
“…By generating free carboxylic groups, PMEs also affect the wall pH and consequently influence the activity of a wide range of hydrolytic enzymes, including PMEs (Grignon and Sentenac, 1991;Denes et al, 2000;Goldberg et al, 2001). PMEs produced by plants take part in important physiological processes, such as microsporogenesis, pollen growth, seed germination, root development, polarity of leaf growth, stem elongation, fruit ripening, and loss of tissue integrity (Tieman and Handa, 1994;Wen et al, 1999;Micheli et al, 2000;Pilling et al, 2000;Micheli, 2001;Pilling et al, 2004). They have also been reported to play a role in response to fungal pathogens (Wietholter et al, 2003) and are required for the systemic spread of Tobacco mosaic virus through the plant (Dorokhov et al, 1999;Chen et al, 2000;Chen and Citovsky, 2003).…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, the exogenous application of small molecule inhibitors offers a method for fine control of enzymatic activity during isolated life stages and tissues. Previous work using antisense technology to inhibit PME (e.g., Pilling et al, 2004) has shown systemic effects of PME inhibition, but are difficult to confine to particular plant parts or life stages, nor are they tractable for field experiments on non-model systems. Therefore, we endeavored to identify appropriate small molecules that have shown efficacy as enzymatic inhibitors, as a starting point for identifying candidate PME inhibitors.…”
Section: Introductionmentioning
confidence: 99%